Observation on the Curative Effect of Microsurgery in 154 Children with Strabismus and Analysis of Its Influencing Factors. (18th October 2021) - Zhao, Zhihua; Li, Kejun; Ma, Qingmin; Zhao, Xiaobin; Jia, Zhiyang
Abstract : Strabismus is a common ophthalmic disease in the process of child body development, in which the two eyes cannot gaze at the target at the same time, and the incidence of this disease of children is higher. In children with esotropia, exotropia, and up and down strabismus and other typical symptoms, the cause is genetic, innerve, and refractive and regulated, and not receiving timely treatment may lead to stereo vision and diplopia and other phenomena, affecting their learning and life. Surgical treatment is the main treatment for strabismus at present. Traditional orthodontic surgery is performed by doctors under the naked eye, often due to improper operation or suture error and other factors, resulting in more postoperative complications, such as more tissue damage, conjunctival congestion, and muscle suture reaction, which seriously affect the clinical effect of surgical treatment. In recent years, with the continuous development of microsurgical technology, the correction of strabismus under a microscope has been widely carried out in clinic. The operation under the microscope makes the operation more delicate and accurate, overcomes the defects of traditional surgery, and highlights the advantages of minimally invasive surgery. The purpose of this study was to investigate the effect of microsurgical techniques in the treatment of strabismus in children and to analyze the factors influencing the outcome. The results showed that microsurgical strabismus correction in the treatment of strabismus children has short operation time, less intraoperative blood loss, short hospital stay, high efficiency, and less complications, which is worthy of popularization. Age, preoperative strabismus angle, refractive error, distance stereopsis injury, near stereoscopic injury, and duration of disease were all independent influencing factors of postoperative efficacy.